2019
DOI: 10.1080/1331677x.2019.1645714
|View full text |Cite
|
Sign up to set email alerts
|

Banking stability during the economic transformation process in selected countries of the Western Balkans

Abstract: Economic transformation is still an ongoing process in many European countries. Despite common economic roots, the current economic situations are developing differently in different countries. This article will consider the process of economic transformation in terms of the banking sector. It aims to assess the level of banking stability throughout the transformation process in the Western Balkan region, and to assess the determinates of banking stability. A tool based on the Macroeconomic Stability Pentagon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…The results obtained are in line with the research conducted by Radulescu, Serbanescu & Sinisi (2019) which showed that the impact of domestic investment on GDP growth is weaker than the impact of private and public consumption, and that the correlation between FDI and economic growth is very weak. Another standpoint confirmed was that of Kubiszewska (2019), stating that the banking sector also affects investments, and that the amount of savings is affected by the state of the budget, or rather, debt (Rant, Mrak & Marinch, 2020). The results confirmed Madžar's view (2019)…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained are in line with the research conducted by Radulescu, Serbanescu & Sinisi (2019) which showed that the impact of domestic investment on GDP growth is weaker than the impact of private and public consumption, and that the correlation between FDI and economic growth is very weak. Another standpoint confirmed was that of Kubiszewska (2019), stating that the banking sector also affects investments, and that the amount of savings is affected by the state of the budget, or rather, debt (Rant, Mrak & Marinch, 2020). The results confirmed Madžar's view (2019)…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study on financial cycles shows they differ across countries and group of countries (developed, developing, transitional). Banking stability is also important determinant in the Minsky's momentum and this is particularly true for transitional economies (Kubiszewska, 2019).…”
Section: Introductionmentioning
confidence: 99%